(untitled) (Research, Society and Development, 2023)
This study aims to identify in the national literature the mental health care of professionals in times of a pandemic, especially biomedical professionals, with the aim of preventing mental health problems. An integrative literature review was carried out with studies available on the BIREME portal. The research took place from February to June 2023. The articles were selected according to the terms: “mental health”, “psychological exhaustion”, “health personnel” and “COVID-19”, with the aid of the Boolean operator ’AND’. The selected articles were published between the last four years (2019 to 2022), made available in full for free and published in the Portuguese language. Six articles that met the inclusion criteria were selected and analyzed. Data were analyzed descriptively, evaluating indicators of suffering and pleasure in frontline health workers. In the studies addressed, signs of anxiety, stress rates, depression and high levels of burnout were identified, the combination of these characteristics led to high expectations and a greater number of frustrations. Health professionals play a fundamental role in health care, with the purpose of guaranteeing safety and ensuring mental well-being, that is, they can generate a healthy work environment not only for themselves, but also for patients who need it. service. In this way, collaborating with the knowledge that needs to be used in attitudes of advances in awareness and prevention of mental illness among professionals.